2007
DOI: 10.1080/00420980701667177
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital, Higher Education and Graduate Migration: An Analysis of Scottish and Welsh Students

Abstract: This paper reports on a model of the sequential migration behaviour of some 76 000 Scottish and Welsh students, from their domicile location to the location of their higher education and on to their employment location. A logit model methodology is employed to analyse the choice of the location of the university attended, whether inside or outside Scotland or Wales. Then, within a GIS framework, migration-on-migration correlations and elasticities are estimated in order to identify the mobility effects of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 40 publications
7
147
0
10
Order By: Relevance
“…This translated into between 18% and 82% of out-of-region students in the university regions. Whether a region hosts a large share of students from other regions is an important variable as there is empirical evidence that the propensity to migrate is higher for those graduates who have migrated before (DaVanzo 1976, Faggian et al 2007a. After finishing university, graduates typically enter the labor market.…”
Section: Migration Between School University and Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This translated into between 18% and 82% of out-of-region students in the university regions. Whether a region hosts a large share of students from other regions is an important variable as there is empirical evidence that the propensity to migrate is higher for those graduates who have migrated before (DaVanzo 1976, Faggian et al 2007a. After finishing university, graduates typically enter the labor market.…”
Section: Migration Between School University and Employmentmentioning
confidence: 99%
“…Yet, most of the empirical evidence is based on location choice at labor market entry only. Faggian et al (2007a) and Faggian and McCann (2009) analyze the migration behavior of UK students from high school to university and from university to first employment. Their findings suggest that most of the British graduates are highly mobile at both stages even on the NUTS 1 level.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been progressively shifting their focus to the youngest age cohorts associated with the very first education and migration decisions [Smith, Rérat, Sage, 2014]. Such decisions impact greatly on the entire futures of young people and the spatial distribution of human capital as such [Faggian, McCann, 2009;Faggian, McCann, Sheppard, 2007;Mulder, Clark, 2002]. Competing for the most talented students becomes an important factor of development for the regions [Findlay, 2011].…”
Section: G Larina Analysis Of Real-world Math Problems: Theoretical mentioning
confidence: 99%
“…(Faggian, McCann & Sheppard, 2007, p. 2523) Therefore, they consider that "the combination of these findings suggests that, on graduating from higher education, the dominant effect of human capital acquisition among the Welsh and Scottish students is therefore that it improves their ability to gain higher-quality employment in a much broader set of locations" (Faggian, McCann & Sheppard, 2007, p. 2523. Dreher and Poutvaara (2011) found that the foreign students have a positive effect on migration because hosting them and offering educational incentives could be an easy way to make them future permanent residents.…”
Section: Introductionmentioning
confidence: 99%
“…Another research made by Faggian et al (2007) on more than 75.000 Scottish-domiciled and Welsh-domiciled students found that the migration behaviour is associated with "both the individual's previous migration history and the level of human capital acquired by the individual." (Faggian, McCann & Sheppard, 2007, p. 2523) Therefore, they consider that "the combination of these findings suggests that, on graduating from higher education, the dominant effect of human capital acquisition among the Welsh and Scottish students is therefore that it improves their ability to gain higher-quality employment in a much broader set of locations" (Faggian, McCann & Sheppard, 2007, p. 2523.…”
Section: Introductionmentioning
confidence: 99%